Effect of yoga and diet on cognitive functions among hypertensives: a review - Arsheen Hasan; Neha Saboo; Sudhanshu Kacker (MGM Journal of Medical Sciences)
Hypertension (HTN), often referred to as a “silent culprit behind multiple bodily dysfunctions,” is a growing global health burden, with its prevalence rising daily. Among its many complications, cognitive dysfunction in hypertensive individuals remains largely unnoticed, impacting daily life and personality traits. Unhealthy lifestyle choices and poor dietary habits further heighten the risk of cognitive impairment. Global research highlights the significant role of yoga and a balanced diet in reducing the risk of cognitive decline among individuals with HTN. Yoga originated in India over 5000 years ago and has become vital to a healthy lifestyle. Dietary factors, such as excessive salt and sugar intake, physical inactivity, obesity, smoking, and alcohol consumption, are key modifiable risk factors for HTN. However, only a limited number of studies have explored the impact of yoga and diet on cognitive function in hypertensive individuals. This review aims to emphasize the role of yoga and diet in addressing oxidative stress and inflammation, which contribute to the pathogenesis of HTN. By focusing on lifestyle modifications, this article seeks to raise awareness about the benefits of yoga and diet in mitigating the overall risk of cardiovascular (CV) diseases. Cognitive function will be assessed using event-related potential P300, mini-mental state examination, and Montreal Cognitive Assessment A and B, while quality of life will be measured using the Quality of Life Scale and stress levels using the Perceived Stress Score. Yoga has been widely recognized for its therapeutic benefits in enhancing immunity and aiding in managing chronic conditions such as CV, respiratory and endocrine disorders, obesity, cancer, and metabolic syndrome. Specific yoga practices, including asanas (postures), pranayama (breathing exercises), and dhyana (meditation), strengthen the immune system, regulate inflammation, and help prevent chronic diseases. These techniques effectively reduce both the psychological and physiological impact of chronic stress. Given the rising burden of lifestyle-related diseases, integrating yoga and dietary modifications into daily routines can significantly improve chronic disease management and overall well-being.